Branding Strategies of Educational Institutions in Increasing the Interest of Applicants: A Case Study of Ma'had Uthman bin Affan - Muhammmad Hirsan Wahudi; Muammar (UIN Mataram, 2026)
This research examines the integrated branding strategies employed by Ma'had Uthman bin Affan, a premier Islamic educational institution in West Nusa Tenggara, Indonesia, to increase applicant interest and institutional competitiveness. Using a descriptive qualitative case study methodology, we conducted in-depth interviews with institutional leaders, marketing personnel, and alumni, supplemented by documentary analysis and institutional data. Findings reveal four interconnected primary branding strategies: (1) Islamic value-centered brand identity construction, (2) strategic and consistent social media engagement and digital marketing, (3) institutionalized alumni networks functioning as brand ambassadors, and (4) continuous educational quality improvement as tangible brand proof. The institution achieved a 68.4% increase in applicants over the 2021–2025 period, with accelerating growth trajectories in recent years. Theoretically, findings align with Aaker's brand equity framework, demonstrating that integrated brand management transcends marketing communication to encompass organizational culture and service delivery excellence. The research contributes to educational marketing theory by establishing that value-based differentiation combined with authentic service quality creates sustainable competitive advantage in Islamic educational markets. Results have significant implications for institutional leaders seeking to strengthen market positioning while maintaining spiritual and academic missions. The study recommends that Islamic educational institutions adopt comprehensive integrated brand management approaches positioning Islamic values as central competitive differentiation mechanisms.